Ultra‐Thin Strain‐Relieving Si1−xGex Layers Enabling III‐V Epitaxy on Si - Trevor R. Smith; Spencer McDermott; Vatsalkumar Patel; Ross Anthony; Manu Hedge; Sophie E. Bierer; Sunzhuoran Wang; Andrew P. Knights; Ryan B. Lewis (Advanced Materials Interfaces)
Abstract The explosion of artificial intelligence, the possible end of Moore's law, dawn of quantum computing, and the continued exponential growth of data communications traffic have brought new urgency to the need for laser integration on the diversified Si platform. While diode lasers on group III‐V platforms have long‐powered internet data communications and other optoelectronic technologies, direct integration with Si remains problematic. A paradigm‐shifting solution requires exploring new and unconventional materials and integration approaches. In this work, it is shown that a sub‐10‐nm ultra‐thin Si1−xGex buffer layer fabricated by an oxidative solid‐phase epitaxy process can facilitate extraordinarily efficient strain relaxation. The Si1−xGex layer is formed by ion implanting Ge into Si(111) and selectively oxidizing Si atoms in the resulting ion‐damaged layer, precipitating a fully strain‐relaxed Ge‐rich layer between the Si substrate and surface oxide. The efficient strain relaxation results from the high oxidation temperature, producing a periodic network of dislocations at the substrate interface, coinciding with modulations of the Ge content in the Si1−xGex layer and indicating the presence of defect‐mediated diffusion of Si through the layer. The epitaxial growth of high‐quality GaAs is demonstrated on this ultra‐thin Si1−xGex layer, demonstrating a promising new pathway for integrating III‐V lasers directly on the Si platform.